Sedimentary architecture of shallow and deep subsurface Quaternary sediments, southern Ontario - Slomka, Jessica (My University, 2011)
Architectural element analysis (AEA) is a tool developed by Allen (1983) and Miall (1985) to describe and understand the internal and external geometry of fluvial sedimentary deposits observed in outcrop, and has been applied to a variety of depositional environments. AEA is a valuable methodology for the detailed reconstruction of sedimentary heterogeneity within stratigraphic units and aquifers/aquitards, which is particularly important in areas strongly reliant on groundwater as a potable source of water such as the Georgetown area in southern Ontario.
This thesis involves a detailed facies and architectural analysis of subsurface Quaternary glacial sediments in the Limehouse and Georgetown area of southern Ontario. A local aggregate pit in Limehouse, Ontario provides several well-exposed outcrop faces primarily composed of coarse-grained sand and gravel deposits (Chapter 2). Architectural elements delineated from the outcrop faces in Limehouse serve as an analogue to deeper subsurface sediments recorded from fully-cored boreholes drilled in the Sixteen Mile Creek area of Georgeotwn, Ontario, which is an area devoid of outcrop exposures (Chapter 3). The Quaternary stratigraphy of the Limehouse and Georgetown area is significantly heterogeneous with a complex architecture recorded in both shallow and deep subsurface sediments (Chapters 2, 3). Aquitard and aquifer/recharge zone layers may be discontinuous and incised/truncated in some places, which may form a hydrologic connection between units and through till sheets (considered to be regional aquitards) to underlying aquifer units (Chapters 2, 3). The geometry and architecture of stratigraphic units can improve the understanding of groundwater flow behaviour, contaminant migration pathways and may enhance the accuracy of local and regional three-dimensional geologic and hydrogeologic models in southern Ontario and for similar glaciated terrains elsewhere.